Experience Of Female's Sex Workers Who Are Infected By HIV / AIDS In Buleleng Regency: A Phenomenology Study - Putu Sukma Megaputri; Ketut Putra Sedana; Gede Adi Kristiawan; Ketut Susini; Putu Indrawan (JURNAL KEBIDANAN, 2020)
Indonesia is still in a position of the concentrated epidemic, where female sex workers are still one of the risk populations that are very vulnerable to HIV/AIDS. The process of accepting and living experience of infected female sex workers becomes very important so that the quality of life is better. Buleleng is one of the districts in Bali with the highest incidence of HIV/AIDS by sex workers. The purpose of this study was to determine the life experiences of sex workers when infected with HIV/AIDS in Buleleng Regency. Quality research methods with a phenomenological approach. Participants numbered 5 participants, with 4 sex workers who were infected with HIV/AIDS and 1 holder of an HIV service program at the Sawan Health Center. The sampling technique used purposive sampling with instruments in the form of interview guidelines. Data collection techniques by conducting in-depth interviews. Then the results are analyzed by transcribing and compiling a theme. The results found five major themes, namely risk factors for infection, self-response, social response after infection, condom use behavior, and health insurance with ARV adherence. The conclusion is that more sex workers do not want to disclose their HIV status, then there are still many sex workers who do not have health insurance so that it leads to non-adherence with treatment.